ANALYSIS OF BIOPHYSICAL CHARACTERISTICS IN THE AREA OF SOCIAL FORESTRY (IPHPS) CIKANCUNG, BPKH CIPARAY, KPH BANDUNG SELATAN - Nasihul Fiqhi El Haqque, A'an
IPHPS at BKPH Ciparay is an area that has been given a decree by the Minister of Environment and Forestry since 2018 covering an area of 28 ha. In realizing a sustainable IPHPS area, it is necessary to manage natural resources (biophysical) so that good institutions can be formed. This study aims to examine the biophysical aspects in the form of edaphic factors as environmental carrying capacity, vegetation diversity as a biodiversity aspect, and land cover to analyze the density of vegetation cover in the IPHPS area. To facilitate research, the area is divided into 5 blocks based on florist conditions and land use. An analysis of edaphic factors was carried out which included physical properties, soil chemical properties, and soil macrofauna to analyze soil fertility. Vegetation analysis and field checks are needed to analyze the structure and composition of vegetation in the area. Spatial analysis using Indonesian Topographical Map (RBI) data and Sentinel 2A satellite imagery was carried out to strengthen the observation data. The condition of the soil bearing capacity in the area is considered quite good with bulk density 0.90 g/cm3 with a soil pH of 4.8 – 6.7. The type of soil is Andosol soil which has fertile characteristics. The level of soil macrofauna diversity is at a moderate level. Thick land cover condition with NDVI > 0.4. The IPHPS area has the potential to increase land and commodity productivity.